Evaluation of the Anthropogenic Impacts of Yusufeli Dam in terms of Landscape Planning - Belgin Yılmam; Hilal Turgut (Doğal Afetler ve Çevre Dergisi)
It seems that the destruction of man-made nature, which reached important levels after the second half of the twentieth century, will occupy the world agenda for a long time. The increase in the world population and consequently the increasing need for energy and food have enhanced the pressures and damages on natural resources. These degradations lead to disruptions in the ecosystem functions and sometimes irreversible deterioration in natural balance. This study aims to determine the anthropogenic pressures in the construction and production processes of the Yusufeli Dam. Kılıçkaya, Öğdem, and Yusufeli regions were chosen as the study area because they were affected by the Yusufeli Dam. Satellite images and GIS software were used to determine the anthropogenic effects. As a result of the study, it was determined that the water surface of approximately 33km2 will be formed with the water retention of Yusufeli Dam. After the completion of the Yusufeli Dam, 612ha forest and 62ha agricultural fields will be destroyed. In the assessment of land capability, it was determined that 100% of class I, 69% of class II, 81% of class III, 7% of class IV, 1% of class VI, and 1% of class VII will remain within the dam reservoir area. The new settlement area where Yusufeli district will move has an area of 640ha and consists of three parts. A significant amount of excavation and filling operations have been carried out to create these areas. According to the zoning plan in the new settlement, 21.6 ha for 1300 residences, 9.65 ha for active green areas, and 5.1 ha for passive green areas were planned. In this study, planning suggestions are also presented to minimize the negative consequences of anthropogenic effects caused by Yusufeli Dam.